Pituitary apoplexy as a rare cause of hypoglycemia - a case report - Cabaj, Justyna; Bargieł, Julia; Lewicki, Marcin (Journal of Education, Health and Sport, 2022)
Introduction: Pituitary stroke is a relatively rare emergency in endocrine practice. In majority of patients, deficiencies of at least one hormone secretion are observed, and clinical manifestations in the form of hypotension and hypoglycemia results from insufficient secretion of adrenocorticotropic hormone. The aim of the study is to present a case report of a patient with symptoms of hypotension and hypoglycemia resulting from a pituitary stroke. Case report: A 72-year-old patient with type 2 diabetes, was admitted to the Department of Endocrinology due to severe hypoglycemia and hypotension accompanied by urinary retention. He was initially diagnosed with sulfonylurea-related hypoglycemia. In the physical examination, attention was drawn to the drooping of the left eyelid, suggesting nerve III palsy. An urgent CT examination was performed, which showed no signs of intracranial bleeding, but the blurred outline of the pituitary gland was visualized. Due to the clinical picture, a pituitary stroke was suspected, and an immediate evaluation of the pituitary function was ordered. The results showed decreased levels of ACTH, cortisol, TSH, FT4 and FT3 and patient was diagnosed with hypopituitarism. The MRI imaging showed recent hemorrhagic changes in the pituitary gland, most likely due to macroadenoma. Conclusion: If a pituitary gland stroke is suspected, MRI and laboratory tests, including assessment of hormonal function, should be performed. Treatment consists mainly of hormone replacement, and in some cases surgical treatment. The differential diagnosis mainly includes subarachnoid bleeding and meningitis.